ANALISIS KINERJA KEUANGAN SEKTOR PERBANKAN DI BURSA EFEK INDONESIA SEBELUM DAN SESUDAH DIBERLAKUKAN POJK FINANCIAL TECHNOLOGY - Ahda Sabila Al Faiz, (2022)
This research aims to determine differences in the Financial Performance of the Banking Sector. The sample for this research is the banking sector listed on the Indonesia Stock Exchange from 2014 to 2021, with an observation period of four years before and four years after the implementation of POJK financial technology, and as many as 37 companies were obtained using a non-probability sampling technique. By using SPSS version 28, a normality test was carried out with the Kolmogorov-Smirnov test and the Paired Sample T-Test analysis technique. The research results obtained indicate that there are differences in liquidity and leverage before and after the implementation of POJK financial technology, but no differences in profitability before and after the implementation of the financial technology in the banking sector listed on the Indonesia Stock Exchange.